Remote-facilitated mental simulation to bridge the theory-practice divide. (2nd February 2022) - Corns, Paul; Thomas, Libby
Abstract : Remote simulation in education predates the COVID-19 pandemic, and its more widespread contemporary use can help inform future teaching practices. This article outlines the development of a remote-facilitated mental simulation (RFMS) delivered to second-year paramedic science students at a UK university. This was created using Sprick et al's simulation design model: preparation, briefing, simulation activity, debriefing, reflection and evaluation. Mental simulation is a teaching modality where participants mentally rehearse processes rather than practical skills. Speaking thoughts aloud helps learners to reflect on their thought processes and decision-making. While studies on remote simulation involve a facilitator viewing participants interacting with a simulation, in this study the participants were observers and the facilitator interacted with the simulation equipment. This arrangement may increase access to simulation for learners who do not have access to such facilities. Participants were engaged through group activities and psychological fidelity was maintained by providing real-time streaming of patient observations. The RFMS was evaluated positively by respondents.